Penempatan Rumah Dinas Polisi Republik Indonesia Oleh Purnawirawan Polisi - Marwan, Assor Januarta; Alfons, Saartje Sarah; Irham, Muhammad (CAPITAN: Constitutional Law & Administrative Law Review, 2024)
The placement of a POLRI official residence by a retired officer is something that is not permitted according to the law, this is because the POLRI official residence itself is intended for active police officers. To find out what form of supervision there is over the placement of official residences by retired police officers and what legal consequences arise because of this, this research was conducted with the aim of safeguarding the rights of active police officers regarding placement in official residences. The research method used in this research is normative juridical with a statutory approach, a conceptual approach, a legal history approach and a comparative approach. The legal materials used are primary, secondary and tertiary legal materials which are analyzed qualitatively. The results of the research show that the form of supervision over the placement of POLRI official residences by retired police officers is repressive supervision in the form of disciplinary sanctions such as written warnings, official warnings, and withholding of rights and facilities. The legal consequences that arise for retired police officers who still occupy official residences include legal action in the form of official warnings and even legal action.